2019
DOI: 10.1186/s43055-019-0014-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of ultrasound in evaluation of pharyngeal dysphagia in children with cerebral palsy

Abstract: Background: The aim of this study was to evaluate the clinical reliability of ultrasound (US) examination using relative laryngeal movement of 40% as a cutoff point to diagnose pharyngeal abnormalities of swallowing using ultrasonographic examination in dysphagic cerebral palsy (CP) patients and comparing its results with a flexible fiberoptic endoscope. Methods: Twenty-five cerebral palsy children suffering from clinical dysphagia were included in this study. The rest distance between the thyroid cartilage an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Nine studies reported complete protocols for conducting the US assessment. A complete protocol was predefined as including probe and frequency information and details of probe placement and participant position (Geddes et al ., 2010; Abdelrahman et al ., 2019; Friedman et al ., 2018, 2019; Huang et al ., 2019; Lee et al ., 2018; Sayyid et al ., 2019; Shaath et al ., 2012; Zhang et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine studies reported complete protocols for conducting the US assessment. A complete protocol was predefined as including probe and frequency information and details of probe placement and participant position (Geddes et al ., 2010; Abdelrahman et al ., 2019; Friedman et al ., 2018, 2019; Huang et al ., 2019; Lee et al ., 2018; Sayyid et al ., 2019; Shaath et al ., 2012; Zhang et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…One study (Garcia‐Torres et al ., 2020) did not report frequency information. Use of B‐mode was reported in two studies (Abdelrahman et al ., 2019; Lee et al ., 2018). Mode was not specified in the other studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies used manual labeling [ 14 , 17 , 19 , 20 ] to identify the change in hyoid location, hyoid movement pattern, and maximum displacement during swallowing. Identifying the locations of the hyoid bone in ultrasound images is a laborious and time-consuming task.…”
Section: Introductionmentioning
confidence: 99%